The Effect of Virtual Reality (VR) Relaxation on the Pain Scale During Vascular Access Cannulation Procedures - Eki Yuliarti; Diyanah Syolihan Rinjani Putri; Happy Indri Hapsari (Indonesian Journal of Global Health Research, 2025)
Cannulation is an act of inserting a needle through the skin into a blood vessel (AV Shunt or Femoral) as a means of connecting the vascular circulation and the dialysis machine during the hemodialysis process, cannulation is a procedure that causes psychological problems in the form of anxiety and physical problems in the form of pain due to the insertion of a large needle during hemodialysis. Relaxation training can be done for a limited period of time and usually has no side effects. One of them can use the Guided imagery technique. The purpose of this study was to determine the effect of Virtual Reality (VR) relaxation on the pain scale during the Vascular Access Cannulation procedure for Hemodialysis Patients at Maguan Husada Pracimantoro Hospital. This study used a Pre-experimental research type with One group pretest-posttest design, conducted in the Hemodialysis Room of Maguan Husada Pracimantoro Hospital in March 2024. This study uses purposive sampling techniqu. The sample used was 56 people. The data collection tool used a numeric rating scale pain assessment sheet. The data analysis used was the Wilcoxon analysis. The results of the study showed that pain before Virtual Reality (VR) relaxation was carried out, the average pain of respondents was 5.96. Pain after Virtual Reality (VR) relaxation for 10 minutes 38 seconds was known to have an average pain of respondents on a scale of 3.36. The results of the Wilcoxon Strained Rank Test with a significant value (p value) of 0.000 < 0.005. There is an effect of virtual reality (VR) relaxation on the pain scale during the procedure of installing vascular access cannulation for hemodialysis patients at Maguan Husada Pracimantoro Hospital.